Classification of defaulters in the payment of debt in Islamic banking practices - Hasan, Aznan; Haron, Muhamad Nasir; Mohamed, Mohd Faysal; Mana, Budeeman (IIUM Press, International Islamic University Malaysia, 2017)
This paper discusses the issue of treatment of debt defaulters from SharÊ'ah perspective and its current practices in Islamic banking and finance. In doing so, the paper first explains the concept of debt and its payment obligation from Islamic point of view. The paper also critically reviews the current practice of treating defaulters by Islamic banks. A thorough analysis on various opinions and views of the classical and contemporary jurists in determining the types of defaulters is also provided. The paper concludes that besides the categorization of defaulters to solvent and insolvent in the modern Islamic banking practice, a new category namely, muta'atthir (a solvent debtor who is facing temporary shortage of liquidity) should also be considered. These debtors are not insolvent based on the ratio of their total assets to debts. However, they are in situation of default due to temporary shortage of liquidity that they are facing. Hence, this new category might have its own ruling from Shari'ah point of view in terms of debt settlement and restructuring where it does not carry the ruling of insolvent debtor.